Implementasi Good Governance dalam Penyelenggaraan Pemerintahan di Kelurahan Parangloe Kecamatan Tamalanrea Kota Makassar - Hasriani, Hasriani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2024)
Good Governance in Indonesia is defined as a democratic way of government in which social and economic resources can be managed well for the common interests of the Indonesian people through deliberation and consensus. This opportunity is given to the public to find out various information about how the government runs its affairs which can help them assess how well the government pays attention to the public interest. This research uses descriptive qualitative data collection techniques, namely interviews, observation and documentation. The data sources used are primary data and secondary data, as well as data analysis techniques consisting of data collection, data reduction, data presentation, withdrawal. conclusion and. data verification. The informants involved came from various backgrounds. positions and institutions. Research results with a focus on 1) Implementation of the principles of transparency and accountability in the Parangloe sub-district: (a) Implementation of the principles of transparency with. indicators (i) Provision of clear information about implementation procedures and accountability (ii) Openness of information about finances (iii) Implementation of activities involving the community; (b) Implementation of the principle of accountability with indicators (i) Increased public trust and satisfaction with financial management by sub-district governments (ii) Increased public awareness regarding the right to assess government administration in sub-districts. 2) Factors that influence the implementation of the principles of transparency and accountability in Parangloe sub-district: (a) Factors that influence transparency with indicators (i) communication (ii) resources. (b) Factors that influence accountability with indicators (i) openness and clarity (ii) exemplary leadership (iii) adaptability. The implementation of the principle of transparency in serving the community in Parangloe Village has been carried out well. This is due to the availability of clear information related to government administration that is easily obtained and understood by the public.